A representação feminina madura na comunicação de marca e seu impacto na intenção de compra - Carvalho , Tatiana Bumachar (2024)
This study aims to understand how the dissociation between mature women 45+ self-image and the way they are portrayed by the brands they buy and use impact their self-brand connection and ultimately their purchase intention levels. The starting point is a reflection on stereotypes that entail the concept of feminine ageing and its disconnection with mature women self-identity, especially 45+ women undergoing major changes in life such as menopause, empty nesting or important changes in their physical aspect, health and well-being. To achieve that intent, the study intersects four major subject themes present in literature: representativity and stereotypes, ageism, female ageing, and purchase intention, within the theoretical framework of identity and consumer behavior. To measure the impact of mature female brand representation in their self-brand connection and purchase intention, as well as possible mediating or moderating effects of consumers self-esteem and self-image clarity, a survey containing four different constructs was applied with 450 women 45+, with the conclusions that representativity triggers added brand connection with the consumer as well as ultimately adds value to the business by increasing purchase intention. Self-esteem also plays a major part in mediating that relationship. The reflection sparked by those results contributes to the discussion concerning brands capability of diversifying consumer representation, especially around female ageing, to generate aggregated value to the brand and ultimately the business as well as added social benefits of portraying mature females away from the sometimes crippling simplicity of stereotypes.